Inhibition of Listeria innocua and Brochothrix thermosphacta in vacuum-packaged meat by addition of bacteriocinogenic Lactobacillus curvatus CRL705 and its bacteriocins - Castellano, Patricia Haydee (2006)
Aims: To evaluate the inhibition effectiveness of Lactobacillus curvatus CRL705 used as a bioprotective culture and of its bacteriocins, lactocin 705 and lactocin AL705, against Listeria innocua, Brochothrix thermosphacta and indigenous lactic acid bacteria (LAB) in vacuum-packaged meat stored at 2°C. Methods and Results: The live culture of Lact. curvatus CRL705 as well as synthetic lactocin 705 and purified lactocin AL705 were shown to be similarly effective in preventing the growth of B. thermosphacta and L. innocua in meat discs in contrast to control samples in which these micro-organisms grew rapidly, their numbers increasing by 3.0- and 2.1-log cycles respectively. In addition, indigenous LAB population showed a lower growth rate in the presence of lactocin 705. Bacteriocin activity was detected in the meat discs during 36 days at 2°C irrespective of the biopreservation strategy applied. Changes in pH were not significantly different in meat discs treated with the protective culture when compared with control samples. Conclusions: Lactobacillus curvatus CRL705 and the produced bacteriocins, lactocin 705 and lactocin AL 705, were effective in inhibiting L. innocua and B. thermosphacta. The use of the bioprotective culture in refrigerated vacuum-packaged fresh meat would be more feasible from an economic and legal point of view. Significance and Impact of the Study: Establishment of biopreservation as a method to ensure the microbiological safety of vacuum-packaged fresh meat at 2°C.